REVIEW OF ISLAMIC LAW ON THE CUSTOM OF POSTPONING MARRIAGE DUE TO THE DEATH OF ONE OF THE PARENTS IN JATISARI VILLAGE, KEDUNGREJA DISTRICT, CILACAP REGENCY - Yusuf Aspidin; M. Jamalun Nizar; Ervin Arifudin (International Conference on Humanity Education and Society (ICHES), 2023)
The purpose of this study is to describe and analyze the review of Islamic law on the custom of delaying marriage due to the death of one of the parents. The approach in this research is qualitative and the type uses field research methods. The data sources used are primary data in the form of interviews and secondary data in the form of literature, literature studies. Analysis of the data used is descriptive analysis. The results of the study state that the strong reason for the custom of delaying marriage is still maintained by the community, for those who violate it will receive social sanctions such as ridicule, gossip or material for discussion, and will get disaster. Then, based on the view of customary Islamic law, the postponement of marriage is categorized as 'urf fasid because the custom that is carried out brings more harm than benefits because it will have the potential to cause adultery and immorality.